Pharmaceutical Sciences Encyclopedia 2011
DOI: 10.1002/9780470571224.pse418
|View full text |Cite
|
Sign up to set email alerts
|

New Approaches to the Characterization of Drug Candidates by Solid‐StateNMR

Abstract: Solid‐state NMR (SSNMR) spectroscopy has been found to be very useful technique for pharmaceutical development. This technique is currently applied for the study of pharmaceutical solids, ranging from detailed structural studies of active pharmaceutical ingredients (APIs) forms to analysis of complex drug products and formulations. The study suggests that solid‐state structure of a pharmaceutical product can influence its properties, manufacturability, and stability. It is essential to regulate and control ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 178 publications
0
20
0
Order By: Relevance
“…The possibility of phase separation in the 1:2 tenoxicam– l ‐arginine SDD was assessed using 13 C‐detected 1 H T 1 and T 1ρ relaxation measurements at a single temperature (273 K). 1 H T 1 measurements can detect phase separation if present but cannot directly prove phase association as different phases within a mixture can have coincidentally similar 1 H T 1 relaxation times 48–49. It was previously shown that multiple peaks within a single 13 C‐detected 1 H T 1 saturation‐recovery experiment can be used to estimate a confidence interval (CI), which is useful for determining the likelihood that a particular resonance with a slightly different 1 H T 1 value is statistically meaningful and thus likely to be a separate phase 49,70.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of phase separation in the 1:2 tenoxicam– l ‐arginine SDD was assessed using 13 C‐detected 1 H T 1 and T 1ρ relaxation measurements at a single temperature (273 K). 1 H T 1 measurements can detect phase separation if present but cannot directly prove phase association as different phases within a mixture can have coincidentally similar 1 H T 1 relaxation times 48–49. It was previously shown that multiple peaks within a single 13 C‐detected 1 H T 1 saturation‐recovery experiment can be used to estimate a confidence interval (CI), which is useful for determining the likelihood that a particular resonance with a slightly different 1 H T 1 value is statistically meaningful and thus likely to be a separate phase 49,70.…”
Section: Resultsmentioning
confidence: 99%
“…In the present work, the SDDs are characterized with DSC, X‐ray powder diffraction (XRPD), IR spectroscopy, scanning electron microscopy (SEM), and solid‐state nuclear magnetic resonance (SSNMR). SSNMR is a particularly powerful tool for studies of amorphous materials and interactions between molecular species in formulated drug products 45–48. Recently developed approaches to the study of molecular association using two‐dimensional (2D) SSNMR and spin diffusion effects are applied to probe intermolecular interactions and gain insight into the solid‐state structure of the SDDs 49.…”
Section: Introductionmentioning
confidence: 99%
“…Specialized lineshape fitting routines are used to extract anisotropic parameters and obtain the principal components of tensors of interest, such as the fits shown in Figures 2.1, 2.2 and 2.3. [121][122][123] More details about quantitative processing of SSNMR data for drug development applications, including quantitative spectral analysis, deconvolution and nonlinear fitting of relaxation data, can be found elsewhere. 123 …”
Section: Special Processing Methodsmentioning
confidence: 99%
“…[121][122][123] More details about quantitative processing of SSNMR data for drug development applications, including quantitative spectral analysis, deconvolution and nonlinear fitting of relaxation data, can be found elsewhere. 123 …”
Section: Special Processing Methodsmentioning
confidence: 99%
See 1 more Smart Citation